The severity of phenotype linked to SUCLG1 mutations could be correlated with residual amount of SUCLG1 protein. Issue 10 (7th August 2010) - Rouzier, C; Le Guédard-Méreuze, S; Fragaki, K; Serre, V; Miro, J; Tuffery-Giraud, S; Chaussenot, A; Bannwarth, S; Caruba, C; Ostergaard, E; Pellissier, J-F; Richelme, C; et al.
Abstract : Background: Succinate-CoA ligase deficiency is responsible for encephalomyopathy with mitochondrial DNA depletion and mild methylmalonic aciduria. Mutations in SUCLA2, the gene encoding a β subunit of succinate-CoA ligase, have been reported in 17 patients until now. Mutations in SUCLG1, encoding the α subunit of the enzyme, have been described in two pedigrees only. Methods and findings: In this study, two unrelated patients harbouring three novel pathogenic mutations in SUCLG1 were reported. The first patient had a severe disease at birth. He was compound heterozygous for a missense mutation (p.Pro170Arg) and a c.97+3G>C mutation, which leads to the complete skipping of exon 1 in a minigene expression system. The involvement of SUCLG1 was confirmed by western blot analysis, which showed absence of SUCLG1 protein in fibroblasts. The second patient has a milder phenotype, similar to that of patients with SUCLA2 mutations, and is still alive at 12 years of age. Western blot analysis showed some residual SUCLG1 protein in patient's fibroblasts. Conclusions: Our results suggest that SUCLG1 mutations that lead to complete absence of SUCLG1 protein are responsible for a very severe disorder with antenatal manifestations, whereas a SUCLA2 -like phenotype is found in patients with residual SUCLG1 protein. Furthermore, it is shown that in the absence of SUCLG1 protein, no SUCLA2 protein is found in fibroblasts by western blot analysis. This result is consistent with a degradation of SUCLA2 when its heterodimer partner, SUCLG1, is absent.